2014
DOI: 10.1364/oe.22.00a857
|View full text |Cite
|
Sign up to set email alerts
|

Influence of V-pits on the efficiency droop in InGaN/GaN quantum wells

Abstract: We discuss the influence of V-pits and their energy barrier, originating from its facets of (101¯1) planes, on the luminescence efficiency of InGaN LEDs. Experimental analysis using cathodoluminescence (CL) exhibits that thin facets of V-pits of InGaN quantum wells (QWs) appear to be effective in improving the emission intensity, preventing the injected carriers from recombining non-radiatively with threading dislocations (TDs). Our theoretical calculation based on the self-consistent approach with adopting k⋅… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…This demonstrated that the threading dislocations in the V-shaped pits act as energy barriers for the lateral transport of charge [27]. In 2014, Kim et al discussed the influence of V-pits and their energy barrier originating from its facets of (1011) planes, and it revealed that higher V-pit energy barrier heights in InGaN QWs more efficiently suppress the non-radiative recombination at TDs, thus enhancing the internal quantum efficiency (IQE) [28]. Chang et al applied superlattice layers to manipulate the nanoscale V-pits and obtain the optimum V-pits size to achieve high-efficiency blue wavelength InGaN/GaN LEDs [22].…”
Section: Introductionmentioning
confidence: 99%
“…This demonstrated that the threading dislocations in the V-shaped pits act as energy barriers for the lateral transport of charge [27]. In 2014, Kim et al discussed the influence of V-pits and their energy barrier originating from its facets of (1011) planes, and it revealed that higher V-pit energy barrier heights in InGaN QWs more efficiently suppress the non-radiative recombination at TDs, thus enhancing the internal quantum efficiency (IQE) [28]. Chang et al applied superlattice layers to manipulate the nanoscale V-pits and obtain the optimum V-pits size to achieve high-efficiency blue wavelength InGaN/GaN LEDs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, only a few dark spots and many black points are present in Figure 2d-f. The black points caused by TD may have become nonradiative recombination centers and seriously degraded the LED performance [27]. In short, lower prestrained layers growth temperature led to bigger and more V-pits formed.…”
Section: Monochromatic Analysismentioning
confidence: 99%
“…Studies have reported that V-shaped pits could degrade LED performance by increasing the probability of nonradiative recombination and causing leakage current [12,[23][24][25]. However, some recent studies have revealed that V-shaped pits may be beneficial for InGaN-based LEDs when pit morphology and density are properly controlled [24,26,27]. The optimal V-pit size and opening angle are 200-250 nm and 60 • , respectively, and achieving these parameters can increase light emission efficiency [28][29][30].By contrast, the QCSE caused by interior strain among InGaN/GaN MQWs reduces emission efficiency because of the reduced overlap of wavefunctions between electrons and holes.…”
mentioning
confidence: 99%
“…The most challenging issues in InGaN-based nitride semiconductors include the spatial fluctuation of indium composition and the generation of dislocations at the interface of InGaN-based heterostructures due to the limited solubility of indium atom into GaN because of the difference in the In-N and Ga-N bond length [52][53][54]. Because of dislocations the non-radiative recombination increases, leading to the rapid decrease in the performance of the InGaN-based devices [55,56].…”
Section: Polar Ingan/gan Heterostructuresmentioning
confidence: 99%